An introduction to gerontology - Stuart-Hamilton, Ian (Cambridge University Press, 2011)
"With the world's population getting increasingly older, there has never been a more pressing need for the study of old age and ageing. An Introduction to Gerontology provides a wide-ranging introduction to this important topic. By assuming no prior expert knowledge and avoiding jargon, this book will guide students through all the main subjects in gerontology, covering both traditional areas, such as biological and social ageing, as well as more contemporary areas, such as technology, the arts, sexuality and education of older adults. An Introduction to Gerontology is written by a team of international authors with multidisciplinary backgrounds who draw evidence from a variety of different perspectives and traditions"